The suboptimal fibrinolytic response in COVID‐19 is dictated by high PAI‐1. (21st July 2022) - Whyte, Claire S.; Simpson, Megan; Morrow, Gael B.; Wallace, Carol A.; Mentzer, Alexander J.; Knight, Julian C.; Shapiro, Susan; Curry, Nicola; Bagot, Catherine N.; Watson, Henry; Cooper, Jamie G.; Mutch, Nicola J.
Abstract: Background: Severe COVID‐19 disease is associated with thrombotic complications and extensive fibrin deposition. This study investigates whether the hemostatic complications in COVID‐19 disease arise due to dysregulation of the fibrinolytic system. Methods: This prospective study analyzed fibrinolytic profiles of 113 patients hospitalized with COVID‐19 disease with 24 patients with non‐COVID‐19 respiratory infection and healthy controls. Antigens were quantified by Ella system or ELISA, clot lysis by turbidimetric assay, and plasminogen activator inhibitor‐1 (PAI‐1)/plasmin activity using chromogenic substrates. Clot structure was visualized by confocal microscopy. Results: PAI‐1 and its cofactor, vitronectin, are significantly elevated in patients with COVID‐19 disease compared with those with non‐COVID‐19 respiratory infection and healthy control groups. Thrombin activatable fibrinolysis inhibitor and tissue plasminogen activator were elevated in patients with COVID‐19 disease relative to healthy controls. PAI‐1 and tissue plasminogen activator (tPA) were associated with more severe COVID‐19 disease severity. Clots formed from COVID‐19 plasma demonstrate an altered fibrin network, with attenuated fiber length and increased branching. Functional studies reveal that plasmin generation and clot lysis were markedly attenuated in COVID‐19 disease, while PAI‐1 activity was elevated. Clot lysis time significantly correlated with PAI‐1 levels. Stratification of COVID‐19 samples according to PAI‐1 levels reveals significantly faster lysis when using the PAI‐1 resistant (tPA) variant, tenecteplase, over alteplase lysis. Conclusion: This study shows that the suboptimal fibrinolytic response in COVID‐19 disease is directly attributable to elevated levels of PAI‐1, which attenuate plasmin generation. These data highlight the important prognostic potential of PAI‐1 and the possibility of using pre‐existing drugs, such as tenecteplase, to treat COVID‐19 disease and potentially other respiratory diseases.